Development of a Stack-based Central Processing Unit Using TTLLogic - Shen Lee, Aaron Tang (Universiti Teknologi Petronas, 2006)
The objective of this project is to build a stack-based central processing unit (CPU) using discrete Transistor-Transistor Logic (TTL). FORTH is the software that is to be implemented on the computer system. The scope of this project is limited to developing and building a stack-based FORTH computer system. Wire wrapping was used to construct the CPU and the computer system. The final computer system consists of 9 wire-wrapped Eurocards connected together through a backplane. The project is successful. A fully functional stack-based FORTH computer system has been successfully developed.